"MULTIFACETED" / PRISM / APPLICATION OF THE MODERN TEACHING METHOD (EDUCATION IN THE 21ST CENTURY, 2024)
In the article entitled "Features of the application of the modern polyhedron /prism teaching method", we tried to show the features of the application of the above method, due to the nature of the taught material and the originality of the writer's imaginative system, age groups of students. We have considered several approaches to the use of the "multisensory" method in accordance with the fundamental features of the method.The purpose of the article is to reveal the essence of the above-mentioned method with the help of interesting observations, principles of teaching material in this format, indicating and justifying the advantages due to the relevant features of this method of teaching, the features arising from the purpose of learning.The novelty of the research lies in the consideration of various approaches to the application of the "Multimetric" method, their features. In the above-mentioned teaching method, effective means of analyzing a literary work were considered, by comparing the works of different authors touching on the same topic, the ideological, philosophical and psychological layers of the literary image were.         As a result of the research, we came to the following conclusions: the "multifaceted" teaching method contributes to a deeper analysis of the taught material, the formation of students' skills in building comparative analytical speech, and the development of figurative еmphasized.
Keywords: comparative analytical thinking; the sphere of the subconscious; comparative connections; ideological formulations of questions; philosophical layers